From demonstrative to definite and beyond: the case of nage 那個 in spoken Taiwan Mandarin - Saillard, Claire (Faits de Langue, 2014)
When demonstrative pronouns undergo grammaticalization, they have regularly been shown to evolve into definite or specific articles (Lehmann 2002, De Mulder & Carlier 2001). In a synchronic perspective, it has also been shown that for some languages, demonstrative determiners are not restricted to deictic or anaphoric functions, but may extend their uses to definite or indefinite determination. In modern standard Chinese (putonghua 普通话 in China, guoyu 國語 in Taiwan)2, there is no acknowledged ‘article’ among the inventory of parts of speech. Instead, there exists a pair of demonstratives, zhe 這 being the proximal form and na 那 the distal form. Both can be used as determiners in association with classifiers. Depending on which spoken variety is studied, various semantic and pragmatic extensions of the demonstratives have been described. In this paper, we examine the case of distal demonstrative na 那, particularly when combined with classifier ge 個. We aim to show that its different uses, as described by Huang 1999 and found in our own corpus, pertain to a single semantic-pragmatic continuum. We then propose a set of criteria allowing to discriminate between all these uses in spoken data, revealing fuzzy zones where the distal demonstrative is either ambiguous or may have several values, as may well be the case in a situation of language variation. *** Les cas de grammaticalisation de pronoms démonstratifs donnant naissance à des articles définis sont bien documentés (Lehmann 2002, De Mulder et Carlier 2011). Dans une vision synchronique des choses, il a été noté que les déterminants démonstratifs ne se restreignaient pas à la fonction déictique ou anaphorique, mais pouvaient avoir d’autres emplois qui, selon les langues, allaient du défini à l’indéfini. En chinois standard moderne (putonghua 普通话 en Chine, guoyu 國語 à Taiwan), l’inventaire des déterminants du nom ne fait pas état d’articles, mais il existe une paire de démonstratifs zhe 這 (proximal) et na 那 (distal) qui peuvent être utilisés comme déterminants en association avec des classificateurs. Selon les variétés orales étudiées, diverses constatations ont été faites concernant l’extension sémantique et pragmatique de ces démonstratifs. Dans cet article, nous nous intéressons au cas du distal na 那, et plus particulièrement la combinaison démonstratif + classificateur nage 那個. Nous montrons en quoi ses différentes valeurs, telles que relevées dans des corpus d’interactions orales spontanées (Huang 1999 puis nos propres corpus), peuvent être considérées comme faisant partie d’un continuum sémantico-pragmatique. Nous proposons ensuite des critères permettant de discriminer entre les divers usages de nage 那個 dans les interactions orales, révélant également des zones d’incertitude ou de pluralité des fonctions, typiques d’une situation de variation.